Nutraceuticals and Pharmaceuticals - E. A. Poluektova; A. G. Beniashvili; R. V. Maslennikov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim. To provide a definition and classification of nutraceutical products and to show their significane in modern integrative medicine.Background. Nutraceuticals are foodstuffs and their components, which have a positive effect on human health, including preventive maintenance and treatment of diseases. Nutraceuticals include healthy and functional foods, as well as biologically active food additives (BAFA). Healthy foods are nutritional foodstuffs without any artificial modification. These include organic, whole, and natural foods. Alongside a high nutritional value, functional food products have a positive effect on the human body due to functional food ingredients. BAFAs are food additives that contains one or several food ingredients (vitamins, mineral substances, plant components, amino acids and others). Specialists express conflicting viewpoints concerning nutraceuticals. Some nutraceuticals, such as probiotics, have confirmed their effectiveness in clinical trials, while the beneficial properties of others require further elucidation.Conclusions. The application of nutraceuticals, as well as their combined use with pharmaceuticals, in accordance with recommendations by scientific professional associations formulated on the basis of valid research studies can lead to an improvement in the quality of the life and longevity of the population. This position forms a basis for the development of integrative medicine — a contemporary approach to the treatment of diseases.